2019
DOI: 10.1038/s41598-019-44936-3
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Steady State Response; nature and utility as a translational science tool

Abstract: The auditory steady-state response (ASSR) has been used to detect auditory processing deficits in patients with psychiatric disorders. However, the methodology of ASSR recording from the brain surface has not been standardized in preclinical studies, limiting its use as a translational biomarker. The sites of maximal ASSR in humans are the vertex and/or middle frontal area, although it has been suggested that the auditory cortex is the source of the ASSR. We constructed and validated novel methods for ASSR rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 37 publications
(55 reference statements)
4
46
0
Order By: Relevance
“…WT and Fmr1 -KO rats showed clear ITC and ERSP responses at 10–80 Hz. Peak ITC and ERSP responses observed at 40–50 Hz in the gamma frequency band (30–80 Hz) are consistent with previous reports in rats 32 and humans 15 , 47 , 48 . ASSR recordings revealed clear impairment of ITC at 30–70 Hz in Fmr1 -KO rats compared with WT rats.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…WT and Fmr1 -KO rats showed clear ITC and ERSP responses at 10–80 Hz. Peak ITC and ERSP responses observed at 40–50 Hz in the gamma frequency band (30–80 Hz) are consistent with previous reports in rats 32 and humans 15 , 47 , 48 . ASSR recordings revealed clear impairment of ITC at 30–70 Hz in Fmr1 -KO rats compared with WT rats.…”
Section: Discussionsupporting
confidence: 92%
“…Further, there was also clear impairment of ERSP at 30–60 Hz in Fmr1 -KO rats. We used a previously developed ASSR paradigm that adopted click sounds as stimuli in freely moving rats 32 , with a similar method having been used in subjects with schizophrenia 49 . However, no robust impairment of ERSP in the gamma frequency band has been observed in subjects with FXS or Fmr1 KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some investigators have reported disparate findings, such as increased ASSR in psychosis patients, 46 positive correlations between hallucinations and gamma oscillations, 47 and state‐dependent ASSR switch 48 . In addition, a recent study of graded doses of ketamine has presented a dose‐dependent biphasic ASSR, 49 suggesting that the ASSR abnormalities include both decreased and increased gamma activity. Therefore, it is also possible that the enhanced ASSR of Cyfip2 +/− mice might reflect a pathological condition of the mice rather than augmentation of PFC functions.…”
Section: Discussionmentioning
confidence: 99%
“…e b i o m e d i c i n e . c o m brain structure, in particular in the anterior cingulate cortex and the insula [7], signals from visual [8] and auditory pathways [9]. Both structural changes using MRI approaches and methodologies to explore either visual or auditory pathways are available in mice.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%